The role of meaning and form similarity in translation recognition in highly proficient balanced bilinguals: A behavioral and ERP study. (February 2016) - Moldovan, Cornelia D.; Demestre, Josep; Ferré, Pilar; Sánchez-Casas, Rosa
Abstract: Previous behavioral findings showed that pairs of words that are highly related in meaning across two languages and pairs in which the second word is related in lexical form to the correct translation of the first one produce interference effects when highly proficient balanced bilinguals perform a translation recognition task (Ferré, Sánchez-Casas, & Guasch, 2006; Moldovan, Sánchez-Casas, Demestre, & Ferré, 2012). In contrast, interference effects were not observed when the two words were less related in meaning. The lack of interference with less related words could be explained by the fact that the level of activation of the corresponding semantic representations is too low so as to produce interference at the time the translation decision has to be made. Moreover, behavioral measures might be not sensitive enough to capture the activation of such representations. In the present study, highly proficient balanced Catalan–Spanish bilinguals performed a translation recognition task in which a short stimulus onset asynchrony (SOA, i.e., 250 ms) was used and event related potentials (ERPs) were recorded. There were three critical conditions: pairs of words highly related in meaning, pairs of words less related in meaning, and pairs in which the second word was similar in lexical form to the correct translation of the first word. Behavioral results showed interference effects in all conditions. ERPs revealed modulations of the N400 for the two semantic conditions, and modulations of the LPC for the form condition. These results reveal that when short SOAs and sensitive measures are used, interference effects with words less related in meaning are obtained as well. In addition, these findings suggest that meaning is accessed before the translation equivalent becomes available, that is, highly proficient balanced bilinguals can directly access the conceptual system from both of their languages. Highlights: Balanced bilinguals activate the meaning of a word before activating its translation. Semantically related pairs modulated the amplitude of the N400. The amplitude of the N400 varied as a function of semantic similarity. Translation neighbors elicited an LPC.